Visual culture and feminist graphic activism on instagram in Spain and Latin America - Castro-Martínez, Andrea; Pérez-Ordóñez, Cristina; Torres-Martín, José Luis (My University, 2023)
Visual culture has developed into an important form of communication and knowledge exchange, especially in politics and public interaction, with Instagram as one of its key arenas (Leaver et al., 2020). Using images and illustration, Instagram is used to encourage intergenerational dialogue and attract young people to women's social demands (Feltman & Szymanski, 2018) in the fourth feminist wave (Cochrane, 2015). In this network, many women artists develop graphic activism that, through their self-management (Núñez Domínguez & Vera, 2021), gives visibility to women's problems, demands and struggles (García & Solana, 2019; Suárez-Carballo et al., 2021). This is how they have emerged as feminist influencers and trendsetters. This work studies how Spanish and Latin American female illustrators use Instagram to mobilise and transmit their messages, encouraging a visual culture in service to the women's movement. It also aims to determine what are the common traits of these artists and what are the main visual symbols of their graphic activism. For this purpose, we analyse four self-described feminist illustrators whose Instagram communities have more than 100,000 followers. Documentary review and analysis of the visual content of their profiles between December 2022 and March 2023 are used as methodological tools. The findings reveal the plastic signs used by the artists, their techniques of illustration, their use of colour, composition and framing, as well as the linguistic and iconic symbols they use to construct their digital activism. This represents a good example of graphic activism, in the terms established by Clemente (2012).
Keywords: Artes gráficas; Feminismo; Visual culture; Feminism; Ilustration; Instagram; Graphic activism; Ciberactivism; Female ilustrators